Clonal hematopoiesis: elements associated with clonal expansion and diseases - Ryu, Gangpyo; Koh, Youngil; Jaiswal, Siddhartha; Yoon, Sung-soo (Blood research, 2025)
Clonal hematopoiesis (CH), characterized by the expansion of hematopoietic stem and progenitor cells harboring somatic mutations, has emerged as a significant age-related phenomenon with profound implications for human health. While initially recognized in the 1960s, recent technological advances have revealed its complex nature and widespread prevalence, affecting up to 84% of individuals aged ≥ 70 years. The clinical significance of CH extends beyond its well-established role as a precursor to hematological malignancies, encompassing its association with cardiovascular diseases, chronic kidney disease, and other non-malignant disorders. This comprehensive review synthesizes the current understanding of CH, focusing on recent advances in genetic and molecular mechanisms, particularly the roles of commonly mutated genes such as DNMT3A, TET2, and ASXL1. We address the emerging distinction between myeloid and lymphoid CH, their differential impacts on disease progression, and the complex interplay between CH and inflammation. Special attention is given to newly identified genetic determinants of clonal expansion rates and their implications for disease progression. The review also examines the revolutionary concept of passenger-approximated clonal expansion rate and its utility in understanding CH dynamics. Furthermore, we discuss therapeutic strategies targeting inflammatory pathways and their potential in mitigating CH-associated complications. By integrating recent findings from genetic, molecular, and clinical studies, this review provides a framework for understanding CH as a systemic condition and highlights promising directions for therapeutic interventions.